2017
DOI: 10.5963/jwrhe0601002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Representation of Java Sea Tidal Propagation through Sensitivity Analysis

Abstract: Abstract-Java Sea is a very complex tidal region due to its associated intrinsic geometrical characteristics which include coastline geometry, small islands and sharply varying bottom topography. Several numerical modelling studies have been conducted to evaluate the tidal characteristics of Java Sea. The present modelling study is an attempt to enhance the representation of tidal propagation of Java Sea by performing sensitivity analysis using Delft3D. Several simulations were done with Manning (0.015, 0.018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Currently, the impact of tidal flood is usually modeled using planar approach in geographic information analysis. This approach assumes areas lower than a particular elevation to be inundated utilizing digital elevation model (DEM) and geographic information system (GIS) Tidal hydrodynamics in the Java Sea are complicated, due to their rough shallow bottom topography, diverse types of coastlines, and the interference of tidal waves propagating from the Pacific Ocean, Indian Ocean, and South China Sea [18]. Koropitan and Ikeda [19] previously investigated the implication of the barotropic tides into four tidal harmonic constituents using a three-dimensional (3D) hydrodynamic model combined with observation data and have suggested that the semi-diurnal M 2 component dominates over Java Sea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the impact of tidal flood is usually modeled using planar approach in geographic information analysis. This approach assumes areas lower than a particular elevation to be inundated utilizing digital elevation model (DEM) and geographic information system (GIS) Tidal hydrodynamics in the Java Sea are complicated, due to their rough shallow bottom topography, diverse types of coastlines, and the interference of tidal waves propagating from the Pacific Ocean, Indian Ocean, and South China Sea [18]. Koropitan and Ikeda [19] previously investigated the implication of the barotropic tides into four tidal harmonic constituents using a three-dimensional (3D) hydrodynamic model combined with observation data and have suggested that the semi-diurnal M 2 component dominates over Java Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Koropitan and Ikeda [19] previously investigated the implication of the barotropic tides into four tidal harmonic constituents using a three-dimensional (3D) hydrodynamic model combined with observation data and have suggested that the semi-diurnal M 2 component dominates over Java Sea. Several studies show that wind factor has a minimum contribution to tidal propagation in Java Sea [18][19][20]. Tidal flooding in the northern part of Java periodically rises in July and August during the East Monsoon period [21].…”
Section: Introductionmentioning
confidence: 99%
“…Karimunjawa berada di Laut Jawa sehingga kondisi hidrodinamikanya juga dipengaruhi oleh kondisi hidrodinamika Laut Jawa. Sementara itu hidrodinamika pasang surut di Laut Jawa sangat kompleks, yaitu dipengaruhi gelombang pasang yang merambat dari Samudera Pasifik, Samudera Hindia, dan Laut Cina Selatan (Mustaid & Yanagi, 2013;Hasan & Rambabu, 2017…”
Section: Gambar 1 Area Penelitian Pulau Kemujan Karimunjawaunclassified
“…Pulau Kemujan merupakan salah satu dari 27 gugusan pulau-pulau di Kepulauan Karimunjawa, yang posisinya berada di Laut Jawa. Hidrodinamika pasang surut di Laut Jawa bersifat sangat kompleks, hal ini dikarenakan topografi dasar dangkal yang terjal, garis pantai yang rumit, dan terpengaruh gelombang pasang yang merambat dari Samudera Pasifik, Samudera Hindia, dan Laut Cina Selatan (Hasan & Rambabu, 2017). Penelitian tentang arus di Karimunjawa sudah banyak dilakukan antara lain oleh Ismunarti et al (2016) di Perairan Tanjung Batu Lawang, Karimunjawa, dan Indrayanti et al (2020) di Perairan Pulau Cilik, Karimunjawa; dimana hasil penelitian menunjukkan bahwa perairan tersebut didominasi oleh arus pasang surut.…”
unclassified